1999
DOI: 10.1021/ja990073m
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of 2Fe-2S and 4Fe-4S Clusters in the Anaerobic Ribonucleotide Reductase from Escherichia coli

Abstract: Escherichia coli contains a specific ribonucleotide reductase for deoxyribonucleotide synthesis and growth under anaerobiosis. The R 2 β 2 enzyme contains an iron-sulfur center on its small β 2 subunit that is involved in the one-electron reduction of S-adenosylmethionine and in the generation of a glycyl radical on the large R 2 subunit. By a variety of spectroscopic methods (light absorption, resonance Raman, and Mo ¨ssbauer spectroscopy) and metal and sulfide analysis, it is shown that the metal center is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
79
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 34 publications
13
79
0
Order By: Relevance
“…As frequently observed with some radical SAM enzymes, reconstituted SP lyase preparations were not homogeneous because they contained polypeptides with either a [4Fe-4S] 2ϩ or a [2Fe-2S] 2ϩ cluster, as shown by Mössbauer spectroscopy. In the case (31,33,35). It is likely that this interconversion also occurs in SP lyase.…”
Section: Discussionmentioning
confidence: 95%
“…As frequently observed with some radical SAM enzymes, reconstituted SP lyase preparations were not homogeneous because they contained polypeptides with either a [4Fe-4S] 2ϩ or a [2Fe-2S] 2ϩ cluster, as shown by Mössbauer spectroscopy. In the case (31,33,35). It is likely that this interconversion also occurs in SP lyase.…”
Section: Discussionmentioning
confidence: 95%
“…2A) 2ϩ clusters in other members of the AdoMetdependent radical enzymes, e.g. anaerobic ribonucleotide reductase-activating enzyme (40), pyruvate formate-lyase-activating enzyme (41), biotin synthase (42), and the tRNA-methylthiotransferase MiaB (39). EPR studies only showed a near isotropic S ϭ 1/2 resonance centered near g ϭ 2.01 ( (46), and this was further supported by VTVH MCD saturation magnetization data, which cannot be fit based solely on an S ϭ 1/2 ground state and indicate the presence of Kramers' S Ͼ 1/2 component (Fig.…”
Section: Effect Of Isc and Suf Proteins As Well As The Groes/el Chapementioning
confidence: 99%
“…Class III RNRs represent a third variant and harbors a stable glycyl radical within the so-called NrdD component that also harbors the active site region. An activating component, the 4Fe-4S NrdG protein, has the ability to generate the glycyl radical in NrdD via cleavage of the cofactor AdoMet (7)(8)(9). Class III RNR is an anaerobic enzyme, and the glycyl radical is extremely sensitive to oxygen.…”
mentioning
confidence: 99%